Single high‐energy arc proton therapy with Bragg peak boost (SHARP) - Scott N. Penfold; Alexandre M. C. Santos; Melanie Penfold; Emma Shierlaw; Rosanna Crain (Journal of Medical Radiation Sciences, 2024)
Abstract Introduction Because of the co‐location of critical organs at risk, base of skull tumours require steep dose gradients to achieve the prescribed dosimetric criteria. When available, proton beam therapy (PBT) is often considered a desirable modality for these cases, but in many instances, compromises in target coverage are still required to achieve critical organ at risk (OAR) tolerance doses. A number of techniques have been proposed to further improve the penumbra of PBT. In the current study, we propose a novel, collimator‐free treatment planning technique that combines high‐energy shoot‐through proton beams with conventional Bragg peak spot placement. The small spot size of the high‐energy pencil beams provides a sharp penumbra at the target boundary, and the Bragg peak spots provide a higher linear energy transfer (LET) boost to the target centre. Methods Three base of skull chordoma patients were retrospectively planned with three different PBT treatment planning techniques: (1) conventional intensity‐modulated proton therapy (IMPT); (2) high‐energy proton arc therapy (HE‐PAT); and (3) the novel technique combining HE‐PAT and IMPT, referred to as single high‐energy arc with Bragg peak boost (SHARP). The Monaco 6 treatment planning system was used. Results SHARP was found to improve the PBT penumbra in the plane perpendicular to the HE‐PAT beams. Minimal penumbra differences were observed in the plane of the HE‐PAT beams. SHARP reduced dose‐averaged LET to surrounding organs at risk. Conclusion A novel PBT treatment planning technique was successfully implemented. Initial results indicate the potential for SHARP to improve the penumbra of PBT treatments for base of skull tumours.